1960
DOI: 10.1136/hrt.22.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Priscol on the Pulmonary Circulation in Cor Pulmonale

Abstract: Pulmonary hypertension in chronic pulmonary disease is due mainly to the impairment of the pulmonary vascular bed. It is still doubtful, however, whether neuro-humoral factors also participate in the genesis of this hypertension. Because of the difficulties of the methods that have to be used in the study of this problem, little is known about the autonomous regulation of the lesser circulation in man. Lately there have been some attempts to extend our knowledge in this field by pharmacological investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

1960
1960
1995
1995

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Pressure changes in the lesser circulation were similar to those recorded in our previous work on priscol (Widimsky et al, 1960), but the duration of the hypotensive effect of reserpine was longer. In contrast with the action of priscol, the extent of changes after reserpine did not depend on the initial values.…”
Section: Discussionsupporting
confidence: 85%
“…Pressure changes in the lesser circulation were similar to those recorded in our previous work on priscol (Widimsky et al, 1960), but the duration of the hypotensive effect of reserpine was longer. In contrast with the action of priscol, the extent of changes after reserpine did not depend on the initial values.…”
Section: Discussionsupporting
confidence: 85%
“…In all patients with decompensated cor pulmonale there was a com mon element of an extensive bilateral fibrocirrholic process, the important factor here being the bilaterality. Unilateral disease rarely leads to congestive failure, and we have observed that total unilateral pneumonectomy does not lead to a rise in resting pulmonary artery pressure (see also nor to hyper tension during muscular exercise, as long as the remaining pul monary parenchyma was healthy (38).…”
Section: Pulmonary Hypertensionmentioning
confidence: 95%
“…Pulmonary vascular disease is inferred from the presence of an irreversibly raised resistance, reversibility being assessed by the response of the vascular bed to oxygen or to other vasodilator agents such as tolazoline. 2 Use of the direct Fick principle to measure pulmonary blood flow, on which the assessment of reversibility depends, requires sampling of pulmonary arterial and pulmonary venous blood as well as measurements of metabolic gas exchange. Elegant techniques have been developed for the determination of oxygen consumption in air,3 but simple, rapid, and accurate estimation of gas exchange while the patient breathes 100% oxygen has proved more difficult to achieve.…”
mentioning
confidence: 99%